Anti-flavivirus Properties of Lipid-Lowering Drugs - Farfan-Morales, Carlos Noe; Cordero-Rivera, Carlos Daniel; Reyes-Ruiz, José Manuel; Hurtado-Monzón, Arianna M.; Osuna-Ramos, Juan Fidel; González-González, Arely M.; De Jesús-González, Luis Adrián; Palacios-Rápalo, Selvin Noé; del Ángel, Rosa María (Frontiers in Physiology, 2021)
Although Flaviviruses such as dengue (DENV) and zika (ZIKV) virus are important human pathogens, an effective vaccine or antiviral treatment against them is not available. Hence, the search for new strategies to control flavivirus infections is essential. Several studies have shown that the host lipid metabolism could be an antiviral target because cholesterol and other lipids are required during the replicative cycle of different Flaviviridae family members. In this sense, FDA-approved drugs with hypolipidemic effects could be an alternative for treating flavivirus infections. However, a better understanding of the regulation between host lipid metabolism and signaling pathways triggered during these infections is required. The metabolic pathways related to lipid metabolism modified during DENV and ZIKV infection are analyzed in this review. Additionally, the role of lipid-lowering drugs as safe host-targeted antivirals is discussed.